Tribocorrosion and Mechanical Properties of Nanotubes Grown on Ti–35Nb Alloy by Anodization - Luz, Aline R.; de Lima, Gabriel Goetten; Kasiorowski, Tuany; de Souza, Gelson B.; Lepienski, Carlos M.; Grandini, Carlos R. [UNESP]; Kuromoto, Neide K.; Alves, Ana Paula R. [UNESP] (ASME International, 2024)
In this study, we evaluated the tribocorrosion and mechanical properties of nanotubes grown on a Ti–35Nb alloy. The nanotube arrays, approximately 2.0 µm thick, were formed through controlled anodization and annealing, composed of Ti and Nb oxides. The compact oxide film at the nanotube/substrate interface provided corrosion resistance, lubricating properties in worn tracks, and improved wear resistance. The nanotubes exhibited a lower coefficient of friction, hardness, and elastic modulus compared to untreated Ti–35Nb. The crystalline structure of the nanotubes and the oxide interface layer enhanced adhesion, preventing plastic deformation and improving tribocorrosion resistance.
Keywords: coatings; films; hardness; surface fracture cracking; surface properties and characterization; tribological systems; wear; wear mechanisms